“COVID has Brought Us Closer”: A Proleptic Approach to Understanding ESL Teachers’ Practices in Supporting ELLs In and After the Pandemic - Li, Guofang; Sun, Zhuo (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2023)
This paper uses “prolepsis,” a process of reaching into the past to inform present and future practices, to understand 12 English-as-a-second language (ESL) teachers’ practices of supporting English language learners (ELLs) through remote teaching during the COVID-19 pandemic from 2020-2021 in British Columbia and to envision some different current and future post-pandemic classroom literacies for diverse learners. Accounts of these ESL teachers’ synthetical moments of teaching and supporting ELLs during the pandemic suggest that they had to navigate “new” areas of teaching, including attending to students’ social-emotional learning (SEL), connecting with ELL parents, teaching and engaging students via technology-supported instruction, and co-teaching with mainstream teachers, on the basis of limited or no pre-pandemic experience. These insights suggest a need to widen the focus on ESL teachers’ knowledge and expertise in applied linguistics and instructional strategies to include classroom literacies in integrating SEL into ESL instruction, adopting interactive, student-driven instructional designs and practices afforded by multimodal technologies, maintaining multiple channels of communication with parents and students, and team-teaching with classroom teachers to provide tailored language support for ELLs.